Trade and economic impacts of destination‐based business cash‐flow taxes - Martin, Will (John Wiley & Sons, 2018)
Proposals for destination‐based business cash‐flow taxes (DBCFT) that effectively combine a value‐added tax and a wage subsidy have received enormous attention in the United States and are being proposed as a major tax reform worldwide. Much controversy has focused on trade impacts, but this paper shows that a DBCFT would not create long‐term trade barriers or export subsidies if prices and wages are flexible. It would leave business profits and rents untaxed, providing an unambiguous benefit to foreign investors relative to an origin‐based corporate tax. Domestic wage earners would be compensated for higher prices by the wage deduction, while the position of domestic investors would depend on whether their gains from abolition of origin‐based taxes outweighed their losses from higher consumer prices. A key concern is small, volatile and vulnerable net revenues even with high‐tax rates. At current US consumption and labour shares, a 20% corporate cash‐flow tax with a wage subsidy would generate less than 2% of GDP in net revenues, which could be obtained with much less volatility from a 2.8% consumption tax alone. Under a DBCFT, revenues would become negative if consumption and labour shares returned to their historical norms or if difficult‐to‐tax sectors like owner‐occupied housing were excluded.